2018
DOI: 10.1039/c8cp03918f
|View full text |Cite
|
Sign up to set email alerts
|

Controlling ion transport through nanopores: modeling transistor behavior

Abstract: We present a modeling study of a nanopore-based transistor computed by a mean-field continuum theory (Poisson-Nernst-Planck, PNP) and a hybrid method including particle simulation (Local Equilibrium Monte Carlo, LEMC) that is able to take ionic correlations into account including the finite size of ions. The model is composed of three regions along the pore axis with the left and right regions determining the ionic species that is the main charge carrier, and the central region tuning the concentration of that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 89 publications
6
55
0
Order By: Relevance
“…The electrolyte is modeled in the implicit solvent framework, an approximation common in nanopore modeling studies [1,12,13,14,15,16] and one that captures the device-level physics [17,18]. This work was inspired by our previous study in which we found the presence of scaling [19]. A symmetric charge pattern was used in that study for a model nanofluidic transistor, where current was modulated with the surface charge of the central region.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte is modeled in the implicit solvent framework, an approximation common in nanopore modeling studies [1,12,13,14,15,16] and one that captures the device-level physics [17,18]. This work was inspired by our previous study in which we found the presence of scaling [19]. A symmetric charge pattern was used in that study for a model nanofluidic transistor, where current was modulated with the surface charge of the central region.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, can be prevented by using an appropriately chosen concentration. As we have seen in our previous study [47] for a nanopore transistor, the relevant parameter is R pore /λ D , where R pore is the pore radius somewhere along the pore and λ D is the Debye length. In that paper [47] we showed that device functions scale with the R pore /λ D parameter.…”
Section: Discussionmentioning
confidence: 76%
“…The bulk value is experimental (D bulk K + = 1.849 × 10 −9 m 2 s −1 and D bulk Cl − = D bulk X = 2.032 × 10 −9 m 2 s −1 ), while D pore i just scales the current without influencing the I/I 0 ratio. Following our previous studies [45,8,46,47] here we set the relation D…”
Section: Interparticle Potentialsmentioning
confidence: 99%
See 2 more Smart Citations